Analisis Putusan Hakim Mengenai Perkara Wanprestasi pada Akad Al-Musyarakah Pembiayaan Modal - Fitri Wahidah Rahmah; Dina Madinah; Ahmad Azhari (AL-MASHALIH (Journal of Islamic Law), 2026)
Cases of breach of contract (wanprestasi) often give rise to various legal disputes that are ultimately resolved through litigation before the Religious Courts. The outcomes of these cases vary, with some claims being granted in full, partially granted, or rejected altogether. Such differences depend on the facts of each case and the legal considerations applied by the judges. A problem arises when, in the settlement of breach-of-contract disputes involving Al-Musyarakah capital financing agreements, certain judicial decisions are not entirely consistent with the principles of Islamic Economic Law. This study aims to examine judicial decisions in adjudicating such cases and to analyze these decisions from the perspective of Islamic Economic Law. The researcher employed a qualitative research method, with data sources consisting of judges’ verdict documents, the Qur’an, Hadith, books, journals, theses, relevant laws, and other literature supporting this research. Data collection was carried out through documentation in the form of court verdicts for cases No. 4095/Pdt.G/2022/PA.Sbr and No. 1/Pdt.G.S/2023/PA.Sbr. All data collected were then reduced, presented, and concluded using descriptive analysis techniques. The study found that in case No. 4095/Pdt.G/2022/PA.Sbr, the judge granted most of the plaintiff’s claims while rejecting some petitum. The judge affirmed that the defendant had committed a breach of contract, ordered the defendant to pay off the remaining debt in full, and to cover the court fees. However, the judge rejected the claim requesting the validation of collateral seizure and auction execution by the court. Meanwhile, in case No. 1/Pdt.G.S/2023/PA.Sbr, the judge granted the claim by verstek (in absentia) because the defendant never appeared in court. The judges’ decisions in both cases are in accordance with the provisions on breach of contract outlined in Articles 36 to 39 of the Compilation of Sharia Economic Law (KHES).